O espaço cênico de Lina Bo Bardi: uma poética antropológica e surrealista (ArtCultura, 2008)
Este artigo pretende discutir as práticas antropológicas e surrealistas nos cenários concebidos nos anos 1960 por Lina Bo Bardi. Aplicadas em maior ou menor grau nas cenografias da Ópera dos três tostões, de Brecht (1960), e de Calígula, de Camus (1961), estas práticas atestam a inspiração provocada pelas raízes culturais baianas, mas não impedem que Lina valorize o "distan-ciamento brechtianoâ€?, deixando à mostra as paredes em ruínas do Teatro Castro Alves. Na montagem de Na selva das cidades, de Brecht, (1969), encenada no Teatro Oficina, Lina utilizou lixo reciclado, destruído a cada espetáculo. Busco demonstrar que a dialética de suas práticas denota uma poética fundamentada na dialética entre o antropológico e o vanguardista. PALAVRAS-CHAVE: cenografia; história do teatro; história da cultura.ABSTRACT This article intends to discuss part of the production of designer Lina Bo Bardi, in the years 1969, demonstrating that the author tries to destroy the Metaphysical borders in the act of the glamour of the public. These practices had been applied in greater or lesser degrees in the stage designs of Ópera dos três tostões, by Brecht (1960) and Calígula by Camus (1961), when the inspi-ration came from Bahia cultural roots in a period in which the architect values the question of abandoning illusion as taught by Brecht, and she shows the construction of the scene in the Castro Alves Theater. In the work she did for Na selva das cidades, also by Brecht, (1969), staged in the Oficina Theater, she idealized one ring, where all the used material was made out of recycled garbage, destroyed in the scene during each spectacle. I intend to demonstrate that the dialectic of the practices of Lina denotes a poetical manner based on anthropology and the avant-garde. KEYWORDS: stage-design; history of thea-ter; history of culture.